VALUE OF THE PHYTODRUGS PROLIT AND URISAN IN THE TREATMENT OF GOUTY PATIENTS - A E Ilyina; Viktoria Georgiyevna Barskova (Современная ревматология)
Objective: to study the safety and efficacy of Urisan and Prolit in patients with gout. Subjects and methods. The study enrolled 45 patients who met the Wallace classification criteria for gout, were in the attack-free interval and received no antihyperuricemic therapy. The patients' mean age was 51.2±10.6 years (range 30 to 68 years); the disease duration (median and interquartile range) was 7.0 (6.0; 10.0) years. Intradermal and subcutaneous tophi were present in 33% of the patients. The diagnosis was verified by the detection of sodium monourate crystals in 93%. The patients were divided into 3 groups: 1) those who took Urisan as 2 capsules twice daily; 2) those who received Prolit as 5 capsules thrice daily; 3) those who used Urisan and Prolit in the above doses for a month. Blood biochemical tests for the levels of uric acid (UA), creatinine, urea, aspartate aminotransferase, alanine aminotransferase, and γ-glutamyl transpeptidase, general clinical urinolysis, and daily uricosuria analysis were carried out before and after therapy. Prior to and a month following therapy, the patient's status (the presence of arthritides) was assessed and adverse reactions were recorded. Results. The drugs were well tolerated and no adverse reactions occurred in all the three groups. No disease exacerbations were seen during the study. The values of hepatic and renal functions substantially unchanged. Administration of Urisan resulted in a considerable increase in urine pH (p=0.004). Urine pH was also increased, but statistically insignificantly in Group 3 patients (p=0.09) and decreased in Group 2. Blood UA levels became lower in all the groups. Conclusion. Urisan and Prolit have antihyperuricemic, anti-inflammatory, and litholythic effects and may be recommended for combined therapy of gout.